Fraud detection in public sector institutions: an empirical study in Indonesia - Junaidi; Hendrian; Briyan Efflin Syahputra (Cogent Business & Management, 2024)
In comparison to numerous other ASEAN nations, Indonesia continues to be categorized as a country with a comparatively high number of fraud instances. To reduce future fraud cases, particularly in Indonesia, studies that keep concentrating on examining different aspects and techniques useful in identifying different kinds of fraud is still required. The current study aims to examine how political skill and big data relate to fraud detection. A survey with a quantitative focus was employed for this study. The instrument for gathering data was questionnaires. The study's participants comprised 147 auditors employed with the Financial and Development Supervisory Board of the Republic of Indonesia (BPKP RI) and the Audit Board of the Republic of Indonesia (BPK RI). In this study, structural equation modeling (SEM), with support from the SmartPLS application, is the method of statistical testing. Based on the findings, political skill has been demonstrated to improve fraud detection. This study further establishes the beneficial impact of big data on fraud detection.
Keywords: M41; M42; 650; Fraud; fraud detection; big data; political skill; audit quality